High school agriculture teachers' career satisfaction and reasons they stay in teaching profession - Ismail, Normala; Miller, Greg (Horizon Research Publishing, 2020)
The purpose of the study was to evaluate the reasons why high school agriculture teachers remain in teaching. A descriptive census study was implemented on agriculture teachers (N=252) utilizing an online validated questionnaire in Iowa. A total of 119 agriculture teachers completed the questionnaire with a response rate of 47%. A four-point Likert-type scale from 1=strongly disagree, 2=disagree, 3=agree, and 4=strongly agree was used to measure reasons why teachers stay in the teaching. Mean and standard deviation was 2.88(.32) for overall reasons to stay in teaching demonstrating these reasons influenced teachers to remain in teaching. Findings shows more than half teachers (f=54, 45.4%) plan to remain in teaching for 11 or more years. Further crosstabulates analysis on years of teaching experience variable with three different plans to stay shows that substantial number of late-career teachers plan to stay in short time (50%), 33.7% mid-career teachers plan to stay for 11 or more years, and newly teachers plan to stay for less than 10 years (42.9%). Findings are consistent with literature that reported years of teaching experience which was a predictor for teacher retention.